Placental mitochondrial impairment and its association with maternal metabolic dysfunction - Grismaldo R, Adriana; Luévano-Martínez, Luis A.; Reyes, Monserrat; García-Márquez, Grecia; García-Rivas, Gerardo; Sobrevia, Luis [UNESP] (Wiley, 2024)
The placenta plays an essential role in pregnancy, leading to proper fetal development and growth. As an organ with multiple physiological functions for both mother and fetus, it is a highly energetic and metabolically demanding tissue. Mitochondrial physiology plays a crucial role in the metabolism of this organ and thus any alteration leading to mitochondrial dysfunction has a severe outcome in the development of the fetus. Pregnancy-related pathological states with a mitochondrial dysfunction outcome include preeclampsia and gestational diabetes mellitus. In this review, we address the role of mitochondrial morphology, metabolism and physiology of the placenta during pregnancy, highlighting the roles of the cytotrophoblast and syncytiotrophoblast. We also describe the relationship between preeclampsia, gestational diabetes, gestational diabesity and pre-pregnancy maternal obesity with mitochondrial dysfunction. (Figure presented.).
Keywords: gestational diabetes; metabolic dysfunction; mitochondria; obesity; placenta; preeclampsia; pregnancy